Recent Advances in Hepatocellular Carcinoma Treatment with Radionuclides - Ruiqi Liu; Hong Li; Yihua Qiu; Hongguang Liu; Zhen Cheng (MDPI AG, 2022)
As the third leading cause of cancer death worldwide, hepatocellular carcinoma (HCC) is characterized by late detection, difficult diagnosis and treatment, rapid progression, and poor prognosis. Current treatments for liver cancer include surgical resection, radiofrequency ablation, liver transplantation, chemotherapy, external radiation therapy, and internal radionuclide therapy. Radionuclide therapy is the use of high-energy radiation emitted by radionuclides to eradicate tumor cells, thus achieving the therapeutic effect. Recently, with the continuous development of biomedical technology, the application of radionuclides in treatment of HCC has progressed steadily. This review focuses on three types of radionuclide-based treatment regimens, including transarterial radioembolization (TARE), radioactive seed implantation, and radioimmunotherapy. Their research progress and clinical applications are summarized. The advantages, limitations, and clinical potential of radionuclide treatment of HCC are discussed.